Traditional retail outlets or supermarkets: A probit analysis of shoppers in Trinidad and Tobago - Iton , C. W. Ardon; Scott , Ewan (Applied Studies in Agribusiness and Commerce, 2016)
The purpose of this study is to identify consumers’ retail outlet choice for Roots and Tubers in Trinidad and Tobago between traditional and modern retail outlets, and also to find out what influences consumers’ shopping preferences for one or the other retail format. A Probit model, where both demographics and store attributes were used to predict outlet choice was the methodology utilized in the study. The results obtained suggest that the traditional outlets are the preferred place to purchase Roots and Tubers with 71% of the sample selecting these outlets. Of the fifteen independent variables analyzed in the Probit model, four demographic variables – age, employment status, ethnicity and income – and two latent factors of the store attributes labeled “value” and “location” were statistically significant. Of note, older buyers are 12% more likely to choose the traditional outlet while there is a 16% higher probability that persons in the higher income brackets will choose supermarkets as their retail outlet. These results provide an insight into the choice of outlet of shoppers and the strengths and weaknesses of the two retail formats.JEL code: Q13, M31, C25